p24 Proteins and Quality Control of LIN-12 and GLP-1 Trafficking in Caenorhabditis elegans - Wen, Chenhui (The Rockefeller University Press, 1999)

(untitled)
Mutations in the Caenorhabditis elegans sel-9 gene elevate the activity of lin-12 and glp-1, which encode members of the LIN-12/NOTCH family of receptors. Sequence analysis indicates SEL-9 is one of several C. elegans p24 proteins. Allele-specific genetic interactions suggest that reducing sel-9 activity increases the activity of mutations altering the extracellular domains of LIN-12 or GLP-1. Reducing sel-9 activity restores the trafficking to the plasma membrane of a mutant GLP-1 protein that would otherwise accumulate within the cell. Our results suggest a role for SEL-9 and other p24 proteins in the negative regulation of transport of LIN-12 and GLP-1 to the cell surface, and favor a role for p24 proteins in a quality control mechanism for endoplasmic reticulum–Golgi transport.